A curious case of the necklace hair - Mukherjee Samipa Samir; B S Chandrashekar; R Pavan Raj; Chaithra Shenoy (Wolters Kluwer Medknow Publications, 2016)
Monilethrix is a rare autosomal dominant inheritable hair shaft defect with variable penetrance. The diagnosis is confirmed by the characteristic beaded appearance of the hair under light microscopy which occurs due to defective keratinization. We hereby describe a case of monilethrix syndrome with keratotic follicular papules, moniliform hair, and koilonychias in an 8-year-old Indian female child. A rare association of trichorrhexis nodosa was also noted in our case.